Metomil: investigação eletroquímica e desenvolvimento de metodologias voltamétricas usando eletrodo de diamante dopado com boro - Costa, Daniel Jackson Estevam da (2013)
Methomyl is a carbamate insecticide widely used to control pests in crops. It is a potential contaminant in groundwater (half-life of 50 weeks) showing harmful effects to fish, aquatic invertebrates, and mammals, reported several cases of human poisoning, affecting the central nervous system. In general, involves the analytical chromatographic methods, fluorometric, spectrophotometric fluorescence X-rays, and the use of cyclic voltammetry and amperometric biosensors with gold electrode, demonstrating the use of electrochemical methods for determination of methomyl. This study made use of an electrode of boron-doped diamond due to its intrinsic properties: wide potential window and low adsorption of organic molecules. Thus, we studied the electrochemical behavior of methomyl using CV, SWV and DPV, being proposed methodologies for the determination of methomyl by SWV and DPV. Through the study of pH, determined by means of VPD were observed five oxidation processes (Ep1  + 1,2 V, Ep2  + 1,6 V, Ep3  + 1,8 V, Ep4 ≈ +1,5 V and Ep5  + 0,8 vs. EAg/AgCl) on DDB cathodically polarized, being more sensitive P2. A methodology was developed using VOQ, being the best analysis conditions: pH 3.0 (BR buffer 0.1 mol L-1), f = 35 s 1, Es = 4 mV, Ep = 40 mV, td = 10 s and  = 1500 rpm, obtaining a linear range of 6,6 × 10 5 a 4,2 × 10 4 mol L-1, However, this method did not provide the acceptable recovery at the concentration studied level for methomyl, according to AOAC-I. The VPD technique was used as an alternative for the determination of methomyl. The best conditions for the analysis of VPD that provided the most sensitive voltammetric response were: pH 2.0 (BR buffer 0.1 mol L-1), IT = 0,2 s, Es = 4 mV, Ep = 50 mV, td =10 s and rpm. The material excellent response preconcentrate allowed the development of an analytical with a linearity range from 5.0 × 10-6 to 4.1 × 10-4 mol L-1 with limits of detection and quantification 1.2 × 10-6 and 4.1 × 10-6 mol L-1, respectively. The sensor showed good repeatability (RSD = 1.1%) and reproducibility (RSD = 1.7%), being feasible with recoveries around 87% for commercial formulations.